Studi Perhitungan Pencampuran Batubara Dengan Pemrograman Linear Untuk Memenuhi Kriteria Permintaan Konsumen Di PT. Alamjaya Bara Pratama Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Rifki Amin Ma’sum; Windhu Nugroho; Shalaho Dina Devy (Fakultas Teknik Universitas Cenderawasih, 2024)
Consumer market demand for certain specifications of coal continues to increase every year. However, each coal company has a variety of coal qualities in terms of calorific value, water content, ash content, and total sulfur and so on. PT. Alamjaya Bara Pratama is a coal mining company that has several types of coal products that vary in quality. By coal blending, the aim is to obtain coal product that meet the target with a homogeneous composition and according to consumer coal quality specifications. With the linear programming method for coal blending calculations using the Production and Operation Management - Quantitave Methods software has an influence in maximizing the use of the composition quantity for each type of product (MD and HS) as well as optimizing the quality of the coal blending results. Through POM-QM, it has the advantage of being able to determine the benchmark target value for one of the desired coal quality parameters. With subbitumious coal quality as for the research results are calculations of the final quality for each Mother Vessel, one of which is MV Eastern Camelia with the planning results is (AC 5,0% adb, TS 0,90% adb, GAR 4590 kcal/kg arb) with tonnage requirements for coal products (MD = 29.727,84 MT and HS = 22.772,16 MT). Through the use of linear programming (POM-QM) in calculating coal blending planning, the results are obtained and meet each coal quality parameter limit criterion based on consumer demand.